Exploring University EFL Students’ Use of Communication Strategies in Impromptu Speaking - Handayani, Reli; Sukarno, Berliana Sukma Tri; Perdana, Purnama Rika; Meisani, Diah Royani (Journal of English Language and Education, 2025)
This study examines the role of impromptu speaking in enhancing spontaneous communication skills among university EFL students. The research aims to identify the primary challenges students encounter during impromptu speech and the strategies they utilize before, during, and after the activity. Employing a descriptive qualitative approach, data were gathered through semi-structured interviews and classroom observations involving 44 sixth-semester English major students at Universitas Jambi. Instruments included interview guides and observation checklists. The findings indicate that the main difficulties experienced by students are limited vocabulary, anxiety, poor sentence organization, and unfamiliarity with topics. To address these challenges, students employed various communication strategies, such as simplifying vocabulary, using synonyms, managing anxiety through breathing techniques, and drawing on personal experiences. Post-speech strategies involved vocabulary expansion through reading, regular practice of spontaneous speaking, and seeking peer feedback. The study concludes that despite inherent challenges, impromptu speaking is an effective tool for promoting speaking fluency, confidence, and practical communicative competence. It is recommended that EFL instructors incorporate impromptu speaking activities into their curricula, providing on-going support and strategic guidance to foster students' competence and confidence in speaking.